2019
DOI: 10.1029/2018wr024335
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Vegetation‐Generated Turbulence on the Critical, Near‐Bed, Wave‐Velocity for Sediment Resuspension

Abstract: Laboratory experiments examined the impact of model vegetation on wave‐driven resuspension. Model canopies were constructed from cylinders with three diameters (d = 0.32, 0.64, and 1.26 cm) and 12 densities (cylinders/m2) up to a solid volume fraction (ϕ) of 10%. The sediment bed consisted of spherical grains with d50 = 85 μm. For each experiment, the wave velocity was gradually adjusted by increasing the amplitude of 2‐s waves in a stepwise fashion. A Nortek Vectrino sampled the velocity at z = 1.3 cm above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…Specifically, resuspension in wave flows has been linked to a constant turbulence threshold over a range of stem densities, and a smaller k t(c) has been reported for finer sediment. Tinoco and Coco (2018) observed k t(c) ≈ 7 cm 2 /s 2 for d s = 0.28 mm (Figure 9d in their paper), and Tang et al (2019) measured a smaller threshold (k t(c) ≈ 3 cm 2 /s 2 ) for finer sediment (d s = 85 μm). Compared to this study in unidirectional current, the two oscillatory flow studies report relatively smaller k t(c) , considering their larger grain sizes.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Specifically, resuspension in wave flows has been linked to a constant turbulence threshold over a range of stem densities, and a smaller k t(c) has been reported for finer sediment. Tinoco and Coco (2018) observed k t(c) ≈ 7 cm 2 /s 2 for d s = 0.28 mm (Figure 9d in their paper), and Tang et al (2019) measured a smaller threshold (k t(c) ≈ 3 cm 2 /s 2 ) for finer sediment (d s = 85 μm). Compared to this study in unidirectional current, the two oscillatory flow studies report relatively smaller k t(c) , considering their larger grain sizes.…”
Section: Resultsmentioning
confidence: 88%
“…Tinoco and Coco (2018) observed k t ( c ) ≈ 7 cm 2 /s 2 for d s = 0.28 mm (Figure 9d in their paper), and Tang et al. (2019) measured a smaller threshold ( k t ( c ) ≈ 3 cm 2 /s 2 ) for finer sediment ( d s = 85 μm). Compared to this study in unidirectional current, the two oscillatory flow studies report relatively smaller k t ( c ) , considering their larger grain sizes.…”
Section: Resultsmentioning
confidence: 88%
“…In contrast, for low meadow density (small ah ), near‐bed turbulence may be enhanced by two mechanisms. First, velocity is not significantly diminished within a low‐density meadow, such that individual seagrass shoot may generate turbulence (e.g., Tang et al, 2019; Tinoco & Coco, 2016; Zhang et al, 2018). Second, turbulence generated in the shear layer at the top of the meadow can penetrate to bed and enhance resuspension (Luhar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that near‐bed turbulence, k t , may be a better predictor of sediment transport. For example, the initiation of both bed load and suspended load transport in vegetated channels can be better described by a threshold value of k t than of τ (Tang et al, 2019; Tinoco & Coco, 2018; Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%